Terminal-repeat retrotransposons with GAG domain in plant genomes: a new testimony on the complex world of transposable elements - Chaparro, Cristian (2015)
A novel structure of nonautonomous long terminal repeat (LTR) retrotransposons called terminal repeat with GAG domain (TR-GAG) has been described in plants, both in monocotyledonous, dicotyledonous and basal angiosperm genomes. TR-GAGs are relatively short elements in length (<4 kb) showing the typical features of LTR-retrotransposons. However, they carry only one open reading frame coding for the GAG precursor protein involved for instance in transposition, the assembly, and the packaging of the element into the virus-like particle. GAG precursors show similarities with both Copia and Gypsy GAG proteins, suggesting evolutionary relationships of TR-GAG elements with both families. Despite the lack of the enzymatic machinery required for their mobility, strong evidences suggest that TR-GAGs are still active. TR-GAGs represent ubiquitous nonautonomous structures that could be involved in the molecular diversities of plant genomes.